PERBANDINGAN ASPEK PERLINDUNGAN HUKUM KONSUMEN TERHADAP PRODUK SUSU BAYI KADALUWARSA DI NEGARA INDONESIA DAN KANADA: Comparison of Legal Protection Aspects of Consumers Regarding Expired Baby Milk Products between Indonesia and Canada - Aryadila Martina Wijaya; Nurbaiti, Siti (Faculty of Law, Universitas Trisakti, 2026)
The circulation of expired infant formula products constitutes a serious issue that may endanger the health of infants as a highly vulnerable group of consumers. Therefore, the state has a responsibility to provide adequate legal protection for consumers against unsafe food products. The problem formulation of this study examines how the legal framework governing consumer protection with regard to expired infant formula products is regulated in Indonesia, as well as how consumer legal protection concerning expired infant formula products is regulated in a comparative perspective between Indonesia and Canada. This research employs a normative legal research method using a statutory approach and a comparative law approach. The discussion and conclusions indicate that both Indonesia and Canada have legal regulations that prohibit the distribution of expired infant formula products and require business actors to ensure product safety. However, Indonesia tends to apply consumer protection through law enforcement after violations have occurred, whereas Canada places greater emphasis on a preventive approach